Modificação de nanotubos de carbono por impregnação de nanopartículas metálicas via síntese verde para adsorção de glifosato - Diel, Júlia Cristina (2021)
In the present work, commercial multiwalled carbon nanotubes (MWCNTs) were modified via green synthesis for impregnation of metallic nanoparticles (MPNs), evaluating the influence of plant extracts (pomegranate leaves, eucalyptus leaves and nutshells) as reducing agents, of metal species (copper and iron), the metallic specifications and the type of functionalization (OH and COOH) in the characteristics of the materials. After synthesis, the modified materials were characterized by different techniques, identifying that MWCNTs were resistant to the synthesis process, preserving their structure and morphological characteristics. After characterization, the potential of the materials was evaluated in the removal of the herbicide glyphosate (GLY) by adsorption in an aqueous matrix. MWCNTs impregnated with iron MPNs using nutshells as a reducing agent proved to be more effective in adsorbing GLY, being the material selected to study the effect of pH, kinetic and equilibrium modeling, thermodynamic behavior, of the simulated effluent, material regeneration statistics and physical modeling. The pH test indicates that the best adsorption results were obtained under pH 4, identified as the natural pH of the GLY solution, favoring the process by dispensing with the use of acids or bases for adjustment. Kinetic studies showed a removal percentage of up to 86.23%, for an initial GLY concentration of 35 mg L-1, with the process equilibrium being reached in about 120 min of contact. The kinetic and equilibrium models that best fit the experimental data were Pseudo-first order and Sips, respectively. It was observed that the adsorptive capacity increased with decreasing temperature, indicating that the process was favored at lower temperatures, with the maximum adsorptive capacity found at 43.66 mg g-1 at 298 K. Regarding the application of the material under circumstances In real terms, removals of 68.38% were achieved for effluent A (containing GLY) and 40.33% for effluent B (containing GLY, atrazine and 2,4- D). Furthermore, the adsorbent was applied for six adsorption/regeneration cycles, maintaining similar values of adsorptive capacity in all cycles. To obtain new insights into this process, the experimental equation curves were simulated from statistical physical models and the Hill model with 1 energy and ideal fluid approach presented the best data prediction, indicating that GLY adsorption occurs by formation of a monolayer and that the interactions of adsorbate with the adsorbent are characterized by only one energy. A combination of the system's steric and energetic parameters in relation to its evolution with temperature indicated that it is an exothermic process, inferring the occurrence of a physisorption mechanism, complementing the results obtained by thermodynamic calculations. Finally, the new insights showed that the adsorbent favored the adsorption of the herbicide by the interaction of GLY molecules with the iron MPNs present on the surface of the adsorbent.